The role of pharmacist counseling for patient with type 2 diabetes mellitus and its impact on blood glucose control and quality of life at RSUD Pasar Minggu - Hardi, Devita; Anggriani, Yusi; Purba, Fredrick Dermawan (Faculty of Pharmacy, Universitas Pancasila, 2025)
Quality of life is an important aspect for patients with type 2 diabetes mellitus (T2DM). Pharmacist counseling is a non-pharmacological effort that can be provided to improve quality of life and control blood glucose levels. This study aimed to determine the effect of pharmacist-led therapeutic counseling for T2DM patients on improving their quality of life and reducing blood glucose levels. The study used a quasi-experimental nonequivalent control group design, with pretest and posttest assessments conducted before and after the intervention at RSUD Pasar Minggu, South Jakarta. A total of 194 T2DM patients participated in the study, with 97 patients in both the intervention and control groups. Quality of life was measured using the EQ-5D-5L and EQ-VAS questionnaires, along with fasting blood glucose levels. Measurements were taken three times: before the intervention, and one month and two months after the intervention. Paired data were analyzed using the Wilcoxon test, while unpaired data were analyzed using the Mann-Whitney test at a significance level of 0.05. Counseling significantly improved EQ-5D-5L scores (Δ=0.06; p<0.001) and EQ-VAS scores (Δ=6.40; p<0.001), as well as reduced fasting blood glucose levels (Δ=-12.10 mg/dL; p<0.001) in the intervention group after the intervention. The impact of counseling was particularly significant in the pain/discomfort and anxiety/depression domains. However, no significant correlation was found between quality of life and fasting blood glucose levels in this study (p>0.05). Pharmacist counseling conducted at RSUD Pasar Minggu had a positive and significant impact on improving the quality of life and treatment outcomes related to blood glucose reduction.